Experiencias sobre el estudio de materiales alternativos para modificar asfaltos - Rondon Quintana, Hugo Alexander; Moreno Anselmi, Luis Angel; Rodriguez Urrego, Daniella; Marino, Jennifer Lee (Ingeniería, 2008)
Civil engineers generally use natural materials in order to manufacture and build structural elements, which generates a negative environmental impact. Many countries in the world are replacing natural materials by materials obtained of recycling materials products of industrial processes, construction and mining. These materials (called alternatives in this report) have been used to modify the properties of others. In Colombia, some progresses in this area have been achieved but yet further investigation is needed. In this paper a summary of some studies developed in the area of modified asphalt is presented. The aim of these studies was to evaluate the change in mechanical properties undergoing modified asphalt mixtures with additives of industrial waste products. Most of the materials used to modify the properties of asphalts and asphalt mixtures showed an increase of the mechanical strength of mixtures and the tendency of the modified asphalt is is generally to exhibit lesser thermal sensitivity, increased resistance to flow and stiffness.